2011
DOI: 10.5324/nje.v20i1.1293
|View full text |Cite
|
Sign up to set email alerts
|

Supportive and motivating environments in school: Main factors to make well-being and learning a reality

Abstract: The author examined the relationships between (i) school-related social support from parents, teachers, and classmates, respectively, and students' perceived life satisfaction; and (ii) school-related social support from teachers and classmates and self-reported academic initiative. The analyses were based on data from nationally representative samples of 13-and 15-year-old students from the Norwegian part of the sixth and seventh World Health Organization (WHO) international survey of Health Behavior in Schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(41 reference statements)
0
9
0
3
Order By: Relevance
“…Supportive teacher behavior can significantly predict the life satisfaction of adolescents. Numerous studies have asserted that support from the teacher is an important factor in the adolescent's life satisfaction (Danielsen, 2010;Ferguson et al, 2010;Suldo et al, 2009;Özdemir and Koruklu, 2013;Vieno et al, 2004). The meta-analysis study conducted by Chu et al (2010) found that support obtained from teachers and school personnel is associated with the well-being of adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supportive teacher behavior can significantly predict the life satisfaction of adolescents. Numerous studies have asserted that support from the teacher is an important factor in the adolescent's life satisfaction (Danielsen, 2010;Ferguson et al, 2010;Suldo et al, 2009;Özdemir and Koruklu, 2013;Vieno et al, 2004). The meta-analysis study conducted by Chu et al (2010) found that support obtained from teachers and school personnel is associated with the well-being of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of such a school environment would improve students' educational experiences while boosting their health and well-being (Samdal et al, 1998). In the studies, a positive relationship between teacher support and the life satisfaction of adolescents was found (Danielsen, 2010;Suldo et al, 2009;Ferguson et al, 2010;Özdemir and Koruklu, 2013).…”
Section: Teacher Support School and Life Satisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies exploring students’ well‐being in school usually focus on teachers’ academic support, satisfaction with teachers and the school environment, student relations, classmates’ academic support, and school satisfaction (Chen & Lu, ; Danielsen, ). Konu & Rimpela () developed a conceptual model of students’ well‐being at school.…”
Section: Well‐being In Schoolmentioning
confidence: 99%
“…Laereren er dermed en nøkkelperson for å motivere til laering, og elevenes opplevelse av kompetanse kan støttes ved å gi dem klare forventninger, passende utfordringer og tilbakemeldinger på skolearbeidet (Reeve, 2002). Elevenes opplevelse av tilhørighet til laereren kan påvirke verdien skolearbeidet har for elevene, og fremme deres indre motivasjon (Danielsen, 2010b). Elever som opplever tilhørighet med laereren, ser ut til i større grad å oppleve indre motivasjon, verdi og betydning av skolearbeidet (Niemiec & Ryan, 2009).…”
unclassified